Forecasting corporate distress in the Asian and Pacific region - Russ Moro; Wolfgang Karl Härdle; Saeideh Aliakbari; Linda Hoffmann (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2011)
This study analyses credit default risk for firms in the Asian and Pacific region by applying two methodologies: a Support Vector Machine (SVM) and a logistic regression (Logit). Among different financial ratios suggested as predictors of default, leverage ratios and the company size display a higher discriminating power compared to others. An analysis of the dependencies between PD and financial ratios is provided along with a comparison with Europe (Germany). With respect to forecasting accuracy the SVM has a lower model risk than the Logit on average and displays a more robust performance. This result holds true across different years.
Keywords: C14; G33; C45; 330; credit risk; bankruptcy; Asian companies; SVM; Firmenkundengeschäft; Kreditrisiko; Zahlungsunfähigkeit; Prognoseverfahren; Support Vector Machine; Logit-Modell; Schätzung; Asiatisch-pazifischer Raum